Modern contraceptive prevalence and its predictors among non-refugee and refugee Somali women in Nairobi city, Kenya; a comparative view - Gitonga, Eliphas; Gage, Anastasia J. (Frontiers in Global Women's Health, 2024)
Introduction and methods: This study sought to determine the prevalence and predictors of modern contraceptive use among non-refugee and refugee Somali women in Nairobi City, Kenya. The analysis was based on 976 currently married Somali women aged 15-39 years (non-refugees; 523, refugees; 415) who were interviewed in a 2021 household survey conducted in Kamukunji, Embakasi, and Ruaraka sub-counties of Nairobi City. The analysis was stratified by refugee status and multivariable logistic regression were run to determine predictors of modern contraceptive use in each group.The prevalence of modern contraceptives was 34% for the total sample and 43% and 24% for non-refugees and refugees, respectively. The main methods of contraception among nonrefugees were injectables, implants, and daily pills, while refugees mainly used male condoms, implants, and injectables. Stratified multivariable analysis showed that residence in formal versus informal settlements and salaried employment versus unemployment/relief support were associated with significantly higher odds of modern contraceptive use among non-refugees but significantly lower odds among refugees, after controlling for other factors. Interaction terms confirmed that the strength of the associations of these variables with the odds of modern contraceptive use varied significantly by refugee status.Use of modern methods of contraception was lower among non-refugee and refugee Somali women compared to the national average. and refugee status moderated the association of some predictor variables with the odds of modern contraceptive use. To increase use of modern contraceptives in urban areas, it is recommended that the Ministry of Health, refugee agencies, and county governments engage with the Somali community and implement appropriate interventions to empower refugee women economically and promote their access to and use of voluntary contraception services as soon as they settle in urban areas.